“Am I a priest in the armed forces, or a soldier who is a priest?” Identity work among military chaplains in the Swedish armed forces - Grimell, Jan (Frontiers in Sociology, 2025)
Military chaplains (MCs) in Sweden embody a hybrid professional identity at the intersection of ecclesiastical and military institutions. Ordained Lutheran priests serve within the Swedish Armed Forces, where they may carry arms for self-defense—challenging conventional boundaries between religious and military roles. This study investigates the identity work undertaken by Swedish MCs as they navigate this complex terrain. Based on qualitative data from a 2025 study involving 50 Swedish MCs, this article adopts a narrative approach to understanding identity work in hybrid professional roles. An anonymous qualitative questionnaire enabled participants to reflect openly on their experiences of negotiating the contrasting demands of military and clerical life. The findings reveal that Swedish MCs engage in continuous identity work to maintain clerical integrity while adapting to military culture. Entering the Armed Forces necessitates the deliberate acquisition and internalization of military culture, including its values, hierarchies, practices, and norms, while simultaneously preserving the integrity of the priestly identity, perspective, and commitment. Military culture, shaped by discipline, loyalty, and the potential use of lethal force, both challenges and transforms aspects of MCs’ identities. Carrying weapons intensifies underlying conflicts and constitutes a particularly charged locus of ethical and identity-related tension, which may also generate cognitive dissonance. Furthermore, MCs often inhabit a liminal position, fully belonging neither to the military community nor to the ecclesiastical sphere, which necessitates ongoing negotiation of professional boundaries and personal values. This study contributes to the sociology of hybrid professions and institutional complexity by illustrating how implicit work contracts and organizational cultures shape identity work in boundary-spanning roles. It highlights the need for structured support and reflective practice to sustain professional integrity in such demanding contexts. Future research should adopt longitudinal designs to explore how MCs’ identity work evolves over time, especially in light of shifting geopolitical contexts and increasing demands on their hybrid role.